C Development of Whole Body and Intravascular Near-infrared Optical Molecular Imaging of Markers of Plaque Vulnerablity in Atherosclerosis. (31st May 2014) - Khamis, Ramzi Y; Woollard, Kevin J; Hyde, Gareth D; Boyle, Joseph J; Bicknell, Colin; Hara, Tetsuya; Mauskapf, Adam; Granger, David W; Johnson, Jason L; Ntziachristos, Vasilis; Matthews, Paul M; Jaffer, Farouc A; et al.
Abstract : Background: We aimed to study oxidised low density lipoprotein (oxLDL) as a near infrared fluorescence (NIRF) molecular imaging target, using a monoclonal anti-oxLDL autoantibody (LO1) in mouse and rabbit atherosclerosis models. Methods: LO1 and an IgG3k control antibody were labelled with a NIRF dye to give LO1–750 and IgG3–750. Targeting to atherosclerosis in mice was compared to a reporter of matrix-metalloproteinase activity (MMPSense FAST) by Fluorescence Molecular Tomography (FMT) combined with micro-CT. Uptake by rabbit aorta was detected with a custom-built intra-arterial NIRF catheter, using IVUS for morphological assessment. We further developed LO1 into a molecularly expressed humanised Fab construct with a cysteine-tag (LO1-Fab-Cys). Results: Injection of LO1–750 into high fat (HF) fed Ldlr -/- atherosclerotic mice led to specific focal localization within a region of interest enclosing the aortic arch and its branches. Ex vivo studies confirmed LO1–750 localisation to subendothelium and partially to macrophages within atherosclerotic lesions. Both LO1–750 and the MMP reporter quantified significant increases in arterial targeting related to genotype, age, and duration of HF diet. Following HF diet withdrawal, MMPSense FAST targeting was affected more dramatically, exhibiting a lower intermediate signal than that of LO1–750. In the rabbit, LO1–750 localization was identified in aortic lesions with the intra-arterial catheter. The LO1-Fab-Cys construct localised to atherosclerosis in the mouse model in a similar fashion to the parent antibody. Conclusion: We demonstrated the utility of LO1 and derivative molecularly-expressed constructs, either alone or in combination with other reporters as multi-modality optical imaging agents for the evaluation of atherosclerosis.